Use of Lughatul Fasli among Arabic Language Training Teachers at Sultan Idris Education University - Yakob, Muhammad Helmi (SIBAWAYH Arabic Language and Education, 2023)
The Arabic language curriculum has undergone innovation and change with the implementation of the Primary School Standard Curriculum (KSSR) and the Secondary School Standard Curriculum (KSSM). Through this new curriculum, the use of classroom language in teaching and facilitation (PdPc) was first introduced. Lughatul Fasli is the language of classroom management that is always used by teachers as an intermediate language to convey the content of lessons when interacting with students in class. Through the continuous use of Lughatul Fasli, it is able to increase and foster students' interest in learning Arabic. This study uses a qualitative approach to explore this issue involving 25 Arabic language trainee teachers selected through purposive sampling. Semi-structured interviews were used as a data collection tool. Thematic analysis was conducted using Atlas.ti software. The findings show that the most frequently used types of lughatus fasli speech are expressions of greeting, instructions, questions, and praise. The majority of study participants think that through the use of lughatul fasli language, this can help students to understand the learning content more easily, as well as increase the size of students' vocabulary. In addition, it can also improve the level of communication skills between teachers and students.